Mutual authentication scheme based on the TPM cloud computing platform - Zhen-peng LIU; Feng-long WU; Kai-yu SHANG; Wen-lei CHAI; Xiao WANG (Tongxin xuebao, 2012)
A mutual authentication scheme based on the TPM cloud computing platform was proposed to solve the problem of mutual authentication between user and cloud computing server.Trusted computing technology and traditional smart card password method were used in cloud computing service platform.The scheme completed the authentication of both sides in cloud computing,generated the session key according consulting,at the same time,verified the credibility of cloud service platform.Experiment analysis shows that our scheme can resist various kinds of possible attacks,so it is therefore more secure than other schemes.And the computing time meet the requirements of cloud computing environment.